Analysis of the Role of Iron (Fe) Content on Nickel Distribution in Limonite and Saprolite Zones Using Energy Dispersive X-Ray Fluorescence (ED-XRF) - James William Ariend; Ismail Marzuki (Journal of Green Chemical and Environmental Engineering, 2026)
Nickel (Ni) is a strategic metal widely used in stainless steel, rechargeable batteries, aerospace, and renewable energy technologies. Increasing demand for electric vehicle batteries has intensified exploration of lateritic nickel deposits, which consist of limonite and saprolite horizons with distinct geochemical characteristics. This study investigates the relationship between iron (Fe) and nickel distribution in lateritic profiles using Energy Dispersive X-Ray Fluorescence (ED-XRF). Samples were collected from PT. Genba Multi Mineral, North Morowali, Indonesia, at depths of 1-6 m. Limonite samples were obtained from 1-3 m, while saprolite samples were collected from 4-6 m. After drying, crushing, and sieving to 200 mesh, the samples were analyzed by ED-XRF. The results reveal an inverse relationship between Fe and Ni contents. The limonite zone contained high Fe (48.76-50.23%) but relatively low Ni (0.70-1.15%), whereas the saprolite zone showed lower Fe (21.01-29.41%) and higher Ni (1.45-2.05%). These trends agree with lateritic nickel enrichment processes, in which Fe is concentrated in limonite while Ni becomes enriched in silicate-rich saprolite during weathering. The findings indicate that Fe content is a useful indicator of nickel distribution in lateritic deposits. In addition, ED-XRF proved to be a rapid, non-destructive, and reliable technique for multi-element analysis of laterite samples. This study provides geochemical information that can support nickel exploration, resource evaluation, and mining optimization in lateritic environments.